Evidências de indução de demanda por parto cesáreo no Brasil - Tabi Thuler Santos (2011)
This work investigates the presence of supplier induced demand to the cesarean section before the vaginal delivery, and is used SABESPREV database for the years 2004 to 2009. To assess the incentives for providers to induce demand of cesarean delivery is used the theoretical framework proposed by Gruber et al (1999). Whereas obstetricians receive higher payment for the performance of caesarean section, one of the results of this model is that the amount of induced demand increases with increasing the pay gap between the vaginal and cesarean deliveries. From this result, the paper assesses the empirical model using a logistic regression to measure the impact of the doctors payment gap on the probability of the delivery to be a cesarean delivery. Since there is no contract information for the remuneration of doctors analyzed, the strategy is to build a proxy for the pay gap. The proxy used is the ratio of the value of the births at the hospital where the birth occurred (average cost of caesarean sections performed by SABESPREV with this provider on average cost of SABESPREV with vaginal deliveries for the same provider), taking for granted the basic hypothesis that the doctors pay gap follows the hospitals pay gap. As a result of the empirical exercise is found that the pay gap changes the odds ratio of the mother to perform cesarean section before vaginal birth, as required by the theoretical model. The results presented corroborate existing studies for Brazil, which had already concluded that non-clinical factors are more important role in determining the clinical use of cesarean section in Brazil.